Phase-change composite aerogel material for photothermal conversion and high-density heat storage as well as preparation method and application of phase-change composite aerogel material
By introducing MXenes and CNTs into the aerogel material, the composite phase change material is formed, which solves the problems of low thermal conductivity and reduced phase change enthalpy of traditional phase change materials, and achieves efficient photothermal conversion and heat storage performance.
Patent Information
- Application Number
- CN202411532490.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-30
AI Technical Summary
Traditional organic phase change heat storage materials have disadvantages such as low thermal conductivity, poor photothermal conversion performance and large drop in phase change enthalpy, which limits their application in the fields of solar photothermal conversion and heat storage.
MXenes/CNTs modified aerogel is used as a three-dimensional porous continuous support framework, and a composite aerogel material is formed by combining phase change materials. Through directional freezing and vacuum freeze-drying technology, CNTs and MXene nanosheets are compounded and dispersed in PVA aerogel to form a conductive path network, improving heat transfer performance and interconnection.
It achieves high thermal energy storage density, photothermal conversion efficiency and morphological stability, solves the problems of low thermal conductivity and reduced phase change enthalpy of traditional materials, and improves solar energy utilization and heat storage performance.
Smart Images

Figure CN119391381A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solar thermal conversion and phase change material heat storage, and specifically relates to a phase change composite aerogel material for thermal conversion and high-density heat storage, and a preparation method and application thereof. Background Art
[0002] Renewable energy is gradually replacing most fossil fuels. New renewable energy represented by solar energy is widely considered to be the most important renewable energy due to its significant advantages of being inexhaustible. However, the time and space mismatch problem of solar energy limits its development. Phase change materials can store and release a large amount of thermal energy during the phase change process and are considered to be ideal materials in the field of solar thermal conversion and heat storage.
[0003] Phase change materials (PCMs) as energy storage media can store or release large amounts of energy at a nearly constant temperature during the melting or solidification process, achieving efficient energy utilization and thus reducing CO2 emissions. Common organic PCMs, such as paraffin (PW), polyethylene glycol (PEG), fatty acids, etc., are white substances. When sunlight shines on PCM, the light waves will be reflected, resulting in PCM's poor ability to capture sunlight. Therefore, photothermal conversion materials can be introduced into the field of phase change energy storage. Photothermal conversion materials refer to a class of materials that can convert light energy into thermal energy through their own photothermal conversion mechanism under illumination conditions. The photon capture ability and the design and thermophysical properties of thermal energy storage materials affect the photothermal conversion performance. By compounding photothermal conversion materials with phase change materials, the solar heat absorbed by the photothermal conversion materials can be stored in the phase change materials, achieving comprehensive properties such as high thermal storage capacity, excellent photothermal conversion performance, and good thermal conductivity.
[0004] However, the flammability, volume expansion, leakage, poor thermal conductivity and poor photothermal conversion performance of phase change materials during the phase change process are the main problems hindering the development of phase change materials. Extensive research has focused on new composite phase change materials with shape-stable PCM (ss-PCM), such as preparing ss-PCM by impregnating PCM in a supporting material (e.g., metal foam, microencapsulation). Aerogels have abundant pores that can provide capillary forces, restrict liquid flow, and avoid liquid leakage. Therefore, they are widely used to adsorb liquid phase change materials to form shape-stable composite phase change materials. Two-dimensional transition metal carbides / carbonitrides (MXenes) have broad application prospects in energy conversion and storage. Previous studies have shown that MXenes nanosheets have excellent light absorption properties and can spontaneously convert solar energy into thermal energy. Chinese patent document CN109852349A discloses a light-heat energy conversion and heat energy storage shaped phase change composite material and a preparation method thereof, wherein the composite material is composed of a supporting material and an organic phase change material, wherein the supporting material is Ti2C, Ti3C2, Ti3CN, V2C, Nb2C, TiNbC, Nb4C3, Ta4C3, (Ti 0.5 Nb 0.5 )2C or (V 0.5 Cr 0.5 )3C2 stacked MXenes nanosheets, the organic phase change material is paraffin, fatty acid, fatty acid ester or alcohol compound. In this patented technology, MXene nanosheets and phase change materials are directly mixed, and the improvement of the thermal conductivity of the phase change material is not ideal. At the same time, due to the large amount of MXene nanosheets added, the phase change enthalpy of the material also drops sharply. Summary of the invention
[0005] In view of the defects of the prior art, the purpose of the present invention is to provide a phase change composite aerogel material with good phase change performance and heat transfer performance and a preparation method thereof, so as to solve the shortcomings of traditional organic phase change thermal storage materials such as low thermal conductivity, poor photothermal conversion performance, and large degree of phase change enthalpy decrease.
[0006] To achieve the above purpose, the solution adopted by the present invention is as follows:
[0007] In the first aspect, the present invention provides a phase change composite aerogel material for photothermal conversion and high-density heat storage, characterized in that it is a phase change composite aerogel material with MXenes / CNTs modified aerogel as a three-dimensional porous continuous supporting skeleton and a phase change material as a filling material; wherein, the mass percentage of the phase change composite aerogel material is 100%, the mass percentage of the MXenes / CNTs modified aerogel is 3.0-4.4%, and the mass percentage of the phase change material is 95.6-97.0%.
[0008] Preferably, the phase change enthalpy of the phase change composite aerogel material is 195.2-210.0 J / g.
[0009] Preferably, the phase change material is selected from one or more of monohydric alcohol phase change materials, straight-chain alkane phase change materials, and fatty acid phase change materials; the monohydric alcohol phase change material is selected from one or more of dodecanol, tridecanol, tetradecanol, pentadecanol, and hexadecanol; the straight-chain alkane phase change material is selected from one or more of paraffin, n-pentadecane, n-hexadecane, n-heptadecane, n-octadecane, n-nonadecane, and n-eicosane; the fatty acid phase change material is selected from one or more of palmitic acid, stearic acid, lauric acid, myristic acid, and palmitic acid; preferably, the phase change material is n-eicosane.
[0010] Preferably, the MXenes are selected from Ti2C MXenes, Ti3C2 MXenes, Ti3CN MXenes, V2C MXenes, Nb2C MXenes, TiNbC MXenes, Nb4C3 MXenes, Ta4C3 MXenes, (Ti 0.5 Nb 0.5 )2C MXenes and (V 0.5 Cr 0.5 )One or more of 3C2 MXenes; preferably, the MXenes are Ti3C2 MXenes.
[0011] Preferably, the CNTs are selected from one or more of multi-walled carbon nanotubes, single-walled carbon nanotubes, carboxylated carbon nanotubes and amino carbon nanotubes.
[0012] In a second aspect, the present invention further provides a method for preparing the above-mentioned phase-change composite aerogel material for photothermal conversion and high-density heat storage, comprising the following steps:
[0013] Step (1), adding boric acid and polyvinyl alcohol (PVA) into deionized water, stirring and heating, to obtain a PVA mixed solution;
[0014] Step (2), adding the PVA mixed solution, CNTs, and MXenes dispersion into deionized water according to a certain proportion, stirring and heating, to obtain a stable dispersion;
[0015] Step (3), transferring the dispersion obtained in step (2) into a mold, first pre-freezing it, and then performing vacuum freeze drying to obtain an aerogel material;
[0016] Step (4), impregnating the aerogel material obtained in step (3) into the phase change material in a molten state by vacuum impregnation to obtain a phase change composite aerogel material.
[0017] Preferably, in step (1), the mass ratio of boric acid to polyvinyl alcohol (PVA) is (1-5): (10-30), and the concentration of the formed PVA mixed solution is 30-50 mg / mL; in step (2), the concentration of the MXenes dispersion is 3-7 mg / mL, the volume ratio of the PVA mixed solution, the MXenes dispersion and deionized water is 1: (0.01-0.47): (0.2-0.67), and the mass ratio of MXenes to CNTs is (1-7): 6.
[0018] Preferably, in step (1), boric acid and polyvinyl alcohol (PVA) are first dissolved in deionized water respectively, and then the boric acid solution and the PVA solution are mixed and stirred at 80-100° C. for 5-15 minutes to form a uniform PVA mixed solution; in step (2), the mixture is stirred at 80-100° C. for 30-40 minutes; in step (3), the pre-freezing treatment temperature is -20° C., the pre-freezing treatment time is 5-7 hours, the vacuum freeze drying temperature is -50° C. to -60° C., the vacuum freeze drying time is 45-55 hours, and the vacuum degree is not greater than 15 Pa; in step (4), the vacuum degree of vacuum impregnation is not greater than 20 Pa, the time is 3-5 hours, and the temperature is 60-80° C.
[0019] In a third aspect, the present invention also provides a phase change composite aerogel material prepared by the preparation method as described above.
[0020] In a fourth aspect, the present invention also provides an application of the phase change composite aerogel material as described above in solar thermal conversion and heat storage materials.
[0021] According to the present invention, in a phase change composite aerogel material provided by the present invention, carbon nanotubes (CNTs) have a unique one-dimensional tubular structure, high thermal conductivity and mechanical stability, and two-dimensional transition metal carbides / carbonitrides (MXenes) have excellent light absorption properties and can spontaneously convert solar energy into thermal energy. The present invention uses directional freezing and subsequent freeze drying to composite one-dimensional CNTs and two-dimensional MXene and disperse them in an aerogel formed by PVA. One-dimensional CNTs are used as a conductive "bridge" to connect MXene nanosheets, and a conductive path network is constructed with line-surface contact. Strong π-π interactions improve the interaction between MXene nanosheets, and the interconnected network is synergistically enhanced by CNTs. It can be prepared with high thermal energy storage density, light-to-heat conversion efficiency, and has many advantages such as stable morphology, thermal stability, cyclicity, and excellent safety, and can be widely used in the fields of solar energy conversion and thermal energy storage technology.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) The MXenes / CNTs modified aerogel composite phase change material prepared by the present invention is at the micron level, with MXenes and CNTs attached to its surface and interior, and has a large heat transfer area, good heat transfer performance and good mechanical properties, and a wide range of applications;
[0024] (2) The preparation method of the present invention is simple, and the reaction time and reaction conditions are easy to control;
[0025] (3) The MXenes / CNTs modified aerogel composite phase change material prepared by the preparation method of the present invention has a small amount of MXenes added, and the mass percentage of the MXenes / CNTs modified aerogel is only 3.0-4.4%, which can achieve excellent light-to-heat conversion efficiency. Moreover, the addition of CNTs improves the defect of the modified aerogel composite phase change material obtained by adding only MXenes, that is, the phase change enthalpy decreases significantly;
[0026] (4) The MXenes / CNTs modified aerogel composite phase change material prepared by the present invention is applied to solar energy storage materials. The composite phase change energy storage material shows high sensitivity to light and heat, and has an extremely fast heating rate. It can quickly utilize solar energy to absorb heat, and the utilization rate of solar energy is greatly improved. In addition, it can also solve the problems of volume expansion, significant flow, leakage oxidation and loss of high latent heat that occur during the transformation of the phase change material from solid phase to liquid phase, and has broad application prospects in the field of phase change energy storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The present invention is a schematic diagram of the preparation process of the MXenes / CNTs modified aerogel composite phase change material.
[0028] Figure 2 The cross-section and longitudinal section of the aerogel prepared under the conditions of each embodiment of the present invention and the SEM pictures after impregnation with phase change material. The morphology of the sample was observed by scanning electron microscope (SEM, Hitachi S-4800) at an accelerating voltage of 10.0 kV. Figure 2 (a1), 2(a2), and 2(a3) are SEM images of aerogels without CNTs and MXenes; Figure 2 (b1), 2(b1), and 2(b3) are SEM images of aerogels with added CNTs and 1 mL MXenes; Figure 2 (c1), 2(c2), and 2(c3) are SEM images of aerogels with added CNTs and 5 mL MXenes; Figure 2 (d1), 2(d2) and 2(d3) are SEM images of aerogels with added CNTs and 7mL MXenes.
[0029] Figure 3The XRD patterns of the aerogel composite phase change materials prepared under the conditions of various embodiments of the present invention are shown in Figure 1. The crystal structure of the aerogel sample was analyzed by X-ray diffractometer (XRD, D8 Advance) at a scanning angle (2θ) rate of 2° / min in the range of 5°-80°.
[0030] Figure 4 The FT-IR spectra of the aerogel composite phase change material prepared under the conditions of various embodiments of the present invention are shown in Figure 1. The infrared spectra of the samples were tested using a Fourier transform infrared spectrometer (FT-IR, iS20).
[0031] Figure 5 The DSC curves of the aerogel composite phase change material prepared under the conditions of various embodiments of the present invention are shown in Figure 1. The instrument used is a Diamond DSC differential scanning calorimeter produced by PerkinElmer Instrument Co., Ltd. (heating and cooling range 15-55°C, heating and cooling rate 5°C / min, N2 flow rate 20mL / min). The encapsulation rate of the aerogel composite phase change material can be calculated by the following formula (1):
[0032]
[0033] Figure 6 The light-to-heat conversion curves of the aerogel composite phase change material prepared under the conditions of various embodiments of the present invention are shown.
[0034] Figure 7 The light-to-heat conversion efficiency of the aerogel composite phase change material prepared under the conditions of various embodiments of the present invention is shown in FIG. The light-to-heat conversion efficiency of the aerogel composite phase change material can be calculated by the following formula (2):
[0035]
[0036] Wherein, m is the mass of the composite phase change material, ΔHm is the melting enthalpy of the composite phase change material, P is the light intensity, S is the surface area of the composite phase change material, and Δt is the time difference from the start to the end of the phase change. DETAILED DESCRIPTION
[0037] The present invention provides a MXenes / CNTs modified aerogel composite phase change material for photothermal conversion, and the specific process of the preparation method thereof is as follows: Figure 1 As shown, the following steps are included:
[0038] Step 1: Add boric acid and PVA in a mass ratio of (1-5): (10-30) (3:20 is used as an example in the embodiment of the present invention) into deionized water, stir and heat to prepare a PVA mixed solution;
[0039] In a preferred embodiment, the step is divided into three steps: the first step is to add 300 mg of boric acid to 50 mL of deionized water, and stir for 10 min to obtain a 6 mg / mL boric acid solution; the second step is to add 4000 mg of PVA to 100 mL of deionized water, and stir at 90° C. for 30 min to obtain a 40 mg / mL PVA solution; the third step is to add the boric acid solution to the PVA solution, and stir at 90° C. for 10 min to form a uniform PVA mixed solution;
[0040] Step 2: Add the PVA mixed solution, CNTs, MXenes dispersion solution and deionized water in step 1 into a beaker in proportion, stir and heat to obtain a stable dispersion;
[0041] The concentration of the MXenes dispersion is 3-7 mg / mL (5 mg / mL is taken as an example in the embodiment of the present invention), the volume ratio of the PVA mixed solution, the MXenes dispersion and the deionized water is 1:(0.01-0.47):(0.2-0.67), and the mass ratio of MXenes and CNTs is (1-7):6.
[0042] Step 3: transferring the dispersion obtained in step 2 into a mold for pre-freezing;
[0043] In a preferred embodiment, the pre-freezing treatment is carried out in a freezer; the pre-freezing treatment temperature is -20°C and the time is 6 hours;
[0044] Step 4: vacuum freeze-drying the sample pre-frozen in step 3 to obtain an aerogel material;
[0045] In a preferred embodiment, the vacuum freeze drying temperature is -50 to -60°C, the time is 48 hours, and the vacuum degree is not greater than 15Pa;
[0046] Step 5: Compounding the aerogel material obtained in step 4 with the phase change material by vacuum impregnation;
[0047] In a preferred embodiment, the vacuum degree of the vacuum impregnation is not greater than 20 Pa, the time is 3 to 5 hours, and the temperature is 70°C.
[0048] In a preferred embodiment, the phase change material includes but is not limited to one or more of a monohydric alcohol phase change material, a straight-chain alkane phase change material, and a fatty acid phase change material. The monohydric alcohol phase change material includes but is not limited to one or more of dodecanol, tridecanol, tetradecanol, pentadecanol and hexadecanol. The straight-chain alkane phase change material includes but is not limited to one or more of paraffin, n-pentadecane, n-hexadecane, n-heptadecane, n-octadecane, n-nonadecane and n-eicosane. The fatty acid phase change material includes but is not limited to one or more of palmitic acid, stearic acid, lauric acid, myristic acid and palmitic acid. In an embodiment of the present invention, the phase change material takes n-eicosane as an example.
[0049] In a preferred embodiment, the MXenes include but are not limited to Ti2C MXenes, Ti3C2 MXenes, Ti3CN MXenes, V2C MXenes, Nb2C MXenes, TiNbC MXenes, Nb4C3 MXenes, Ta4C3 MXenes, (Ti 0.5 Nb 0.5 )2C MXenes and (V 0.5 Cr 0.5 )One or more of 3C2 MXenes; preferably, the MXenes are Ti3C2MXenes.
[0050] In a preferred embodiment, the CNTs include, but are not limited to, one or more of multi-walled carbon nanotubes, single-walled carbon nanotubes, carboxylated carbon nanotubes, and amino-treated carbon nanotubes.
[0051] The present invention is further described below in conjunction with examples, the purpose of which is to better understand the content of the present invention and reflect the essential characteristics of the present invention, so the examples cited should not be regarded as limiting the scope of protection of the present invention. It is also particularly pointed out here that the specific experimental methods and equipment involved in the examples are conventional methods or implemented under the conditions recommended by the manufacturer's instructions unless otherwise specified, and the reagents involved are commercially available unless otherwise specified.
[0052] Embodiment 1:
[0053] Step 1: Weigh 300 mg of boric acid and add it to 50 mL of deionized water, stir for 10 min to obtain a 6 mg / mL boric acid solution. Then add 4000 mg of PVA to 100 mL of deionized water, stir at 90°C for 30 min to obtain a 40 mg / mL PVA solution. Then add the boric acid solution to the PVA solution, stir at 90°C for 10 min to form a uniform PVA mixture.
[0054] Step 2: Take 15 mL of the PVA mixed solution obtained in step 1 into a beaker, add 10 mL of deionized water, heat and stir at 90°C for 30 minutes to obtain a stable dispersion.
[0055] Step 3: Pour the dispersion obtained in step 2 into a mold and pre-freeze it in a refrigerator at a pre-freezing temperature of -10°C for 6 hours.
[0056] Step 4: Take out the sample from step 3 and place it in a freeze dryer for vacuum freeze drying to obtain an aerogel material. The vacuum degree of this process is 19 Pa, the vacuum freeze drying temperature is -40°C, and the time is 48 hours.
[0057] Step 5: Compound the sample in step 4 with the phase change material by vacuum impregnation. First, heat n-eicosane in a beaker at 70°C. After the n-eicosane is completely melted, place the prepared aerogel into the melted n-eicosane, and then place the beaker in a vacuum oven for insulation at 70°C for 4 hours. Under negative pressure, liquid n-eicosane fully penetrates into the pores of the aerogel. After filling the aerogel with n-eicosane, filter out the excess n-eicosane liquid on the surface in a ceramic funnel. Finally, a composite phase change material prepared by aerogel is obtained.
[0058] Test results: The mass ratio of the obtained composite phase change material aerogel is 3.0%, and the mass ratio of n-eicosane is 97.0%. The SEM image shows that the aerogel is well arranged, presents continuous folds, has a bridge-like structure, and forms a continuous and interconnected 3D network. There is no obvious dividing line between the aerogel folds after filling the phase change material, indicating that n-eicosane has been completely filled into the microporous structure. From the XRD and FT-IR spectra, it can be seen that except for the characteristic peaks of CNTs and PVA, no new peaks appear, indicating that PVA has no effect on the crystal structure of n-eicosane. From the DSC graph, it can be seen that the melting phase change enthalpy and crystallization phase change enthalpy of the phase change aerogel material reach 209.1J / g and 205.7J / g respectively, the melting temperature and crystallization temperature are 37.5℃ and 31.4℃ respectively, and the corresponding encapsulation rate is 92.4%. The photothermal conversion efficiency is calculated to be 21.51% by the photothermal conversion efficiency formula.
[0059] Embodiment 2:
[0060] Step 1: Weigh 300 mg of boric acid and add it to 50 mL of deionized water, stir for 10 min to obtain a 6 mg / mL boric acid solution. Then add 4000 mg of PVA to 100 mL of deionized water, stir at 90 ° C for 30 min to obtain a 40 mg / mL PVA solution. Then add the boric acid solution to the 40 mg / mL PVA solution, stir at 90 ° C for 10 min to form a uniform PVA mixture.
[0061] Step 2: Take 15 mL of the PVA mixed solution obtained in step 1 into a beaker, add 30 mg of CNTs and 1 mL of MXenes solution (the concentration of the MXenes solution is 5 mg / mL), and finally add 9 mL of deionized water, heat and stir at 90°C for 30 min to obtain a stable dispersion.
[0062] Step 3: Pour the dispersion obtained in step 2 into a mold and pre-freeze it in a refrigerator at a pre-freezing temperature of -10°C for 6 hours.
[0063] Step 4: Take out the sample from step 3 and place it in a freeze dryer for vacuum freeze drying to obtain an aerogel material. The vacuum degree of this process is 15 Pa, the vacuum freeze drying temperature is -55°C, and the time is 48 hours.
[0064] Step 5: Compound the sample in step 4 with the phase change material by vacuum impregnation. First, heat n-eicosane in a beaker at 70°C. After the n-eicosane is completely melted, place the prepared aerogel into the melted n-eicosane, and then place the beaker in a vacuum oven for insulation at 70°C for 4 hours. Under negative pressure, liquid n-eicosane fully penetrates into the pores of the aerogel. After filling the aerogel with n-eicosane, filter out the excess n-eicosane liquid on the surface in a ceramic funnel. Finally, a composite phase change material prepared by aerogel is obtained.
[0065] Test results: The mass ratio of the obtained composite phase change material aerogel is 3.6%, and the mass ratio of n-eicosane is 96.4%. It can be seen from the SEM image that the aerogel is well arranged, presents continuous wrinkles, has a bridge-like structure, forms a continuous and interconnected 3D network, and there is no obvious dividing line between the aerogel wrinkles after filling the phase change material, indicating that n-eicosane has been completely filled into the microporous structure. It can be seen from the XRD and FT-IR spectra that no new peaks appear except the characteristic peaks of CNTs and PVA, indicating that PVA has no effect on the crystal structure of n-eicosane. It can be seen from the DSC graph that the melting phase change enthalpy and crystallization phase change enthalpy of the phase change aerogel material reach 210.0J / g and 207.4J / g respectively, the melting temperature and crystallization temperature are 37.3℃ and 31.4℃ respectively, and the corresponding encapsulation rate is 92.9%. The photothermal conversion efficiency of the sample in Example 2 is increased by 315.6% compared with that in Example 1, reaching 89.39%.
[0066] Embodiment 3:
[0067] Step 1: Weigh 300 mg of boric acid and add it to 50 mL of deionized water, stir for 10 min to obtain a 6 mg / mL boric acid solution. Then add 4000 mg of PVA to 100 mL of deionized water, stir at 90 ° C for 30 min to obtain a 40 mg / mL PVA solution. Then add the boric acid solution to the 40 mg / mL PVA solution, stir at 90 ° C for 10 min to form a uniform PVA mixture.
[0068] Step 2: Take 15 mL of the PVA mixed solution obtained in step 1 into a beaker, add 30 mg of CNTs and 3 mL of MXenes solution (the concentration of the MXenes solution is 5 mg / mL), and finally add 7 mL of deionized water, heat and stir at 90°C for 30 min to obtain a stable dispersion.
[0069] Step 3: Pour the dispersion obtained in step 2 into a mold and pre-freeze it in a refrigerator at a pre-freezing temperature of -10°C for 6 hours.
[0070] Step 4: Take out the sample from step 3 and place it in a freeze dryer for vacuum freeze drying to obtain an aerogel material. The vacuum degree of this process is 15 Pa, the vacuum freeze drying temperature is -55°C, and the time is 48 hours.
[0071] Step 5: Compound the sample in step 4 with the phase change material by vacuum impregnation. First, heat n-eicosane in a beaker at 70°C. After the n-eicosane is completely melted, place the prepared aerogel into the melted n-eicosane, and then place the beaker in a vacuum oven for insulation at 70°C for 4 hours. Under negative pressure, liquid n-eicosane fully penetrates into the pores of the aerogel. After filling the aerogel with n-eicosane, filter out the excess n-eicosane liquid on the surface in a ceramic funnel. Finally, a composite phase change material prepared by aerogel is obtained.
[0072] Test results: The mass ratio of the obtained composite phase change material aerogel is 4.0%, and the mass ratio of n-eicosane is 96.0%. It can be seen from the SEM image that the aerogel is well arranged, presents continuous wrinkles, has a bridge-like structure, forms a continuous and interconnected 3D network, and there is no obvious dividing line between the aerogel wrinkles after filling the phase change material, indicating that n-eicosane has been completely filled into the microporous structure. It can be seen from the XRD and FT-IR spectra that no new peaks appear except for the characteristic peaks of CNTs and PVA, indicating that PVA has no effect on the crystal structure of n-eicosane. It can be seen from the DSC graph that the melting phase change enthalpy and crystallization phase change enthalpy of the phase change aerogel material reach 203.6 J / g and 194.0 J / g respectively, the melting temperature and crystallization temperature are 37.0°C and 31.3°C respectively, and the corresponding encapsulation rate is 89.8%. The photothermal conversion efficiency of the sample in Example 3 is increased by 338.6% compared with that of Example 1, reaching 94.35%.
[0073] Embodiment 4:
[0074] Step 1: Weigh 300 mg of boric acid and add it to 50 mL of deionized water, stir for 10 min to obtain a 6 mg / mL boric acid solution. Then add 4000 mg of PVA to 100 mL of deionized water, stir at 90 ° C for 30 min to obtain a 40 mg / mL PVA solution. Then add the boric acid solution to the 40 mg / mL PVA solution, stir at 90 ° C for 10 min to form a uniform PVA mixture.
[0075] Step 2: Take 15 mL of the PVA mixed solution obtained in step 1 into a beaker, add 30 mg of CNTs and 5 mL of MXenes solution (the concentration of the MXenes solution is 5 mg / mL), and finally add 5 mL of deionized water, heat and stir at 90°C for 30 min to obtain a stable dispersion.
[0076] Step 3: Pour the dispersion obtained in step 2 into a mold and pre-freeze it in a refrigerator at a pre-freezing temperature of -10°C for 6 hours.
[0077] Step 4: Take out the sample from step 3 and place it in a freeze dryer for vacuum freeze drying to obtain an aerogel material. The vacuum degree of this process is 15 Pa, the vacuum freeze drying temperature is -55°C, and the time is 48 hours.
[0078] Step 5: Compound the sample in step 4 with the phase change material by vacuum impregnation. First, heat n-eicosane in a beaker at 70°C. After the n-eicosane is completely melted, place the prepared aerogel into the melted n-eicosane, and then place the beaker in a vacuum oven for insulation at 70°C for 4 hours. Under negative pressure, liquid n-eicosane fully penetrates into the pores of the aerogel. After filling the aerogel with n-eicosane, filter out the excess n-eicosane liquid on the surface in a ceramic funnel. Finally, a composite phase change material prepared by aerogel is obtained.
[0079] Test results: The mass ratio of the obtained composite phase change material aerogel is 4.4%, and the mass ratio of n-eicosane is 95.6%. It can be seen from the SEM image that the aerogel is well arranged, presents continuous wrinkles, has a bridge-like structure, forms a continuous and interconnected 3D network, and there is no obvious dividing line between the aerogel wrinkles after filling the phase change material, indicating that n-eicosane has been completely filled into the microporous structure. It can be seen from the XRD and FT-IR spectra that no new peaks appear except the characteristic peaks of CNTs and PVA, indicating that PVA has no effect on the crystal structure of n-eicosane. It can be seen from the DSC graph that the melting phase change enthalpy and crystallization phase change enthalpy of the phase change aerogel material reach 200.9 J / g and 194.4 J / g respectively, the melting temperature and crystallization temperature are 37.2°C and 31.3°C respectively, and the corresponding encapsulation rate is 88.5%. The photothermal conversion efficiency of the sample in Example 4 is increased by 340.4% compared with that of Example 1, reaching 94.73%.
[0080] Embodiment 5:
[0081] Step 1: Weigh 300 mg of boric acid and add it to 50 mL of deionized water, stir for 10 min to obtain a 6 mg / mL boric acid solution. Then add 4000 mg of PVA to 100 mL of deionized water, stir at 90 ° C for 30 min to obtain a 40 mg / mL PVA solution. Then add the boric acid solution to the 40 mg / mL PVA solution, stir at 90 ° C for 10 min to form a uniform PVA mixture.
[0082] Step 2: Take 15 mL of the PVA mixed solution obtained in step 1 into a beaker, add 30 mg of CNTs and 7 mL of MXenes solution (the concentration of the MXenes solution is 5 mg / mL), and finally add 3 mL of deionized water, heat and stir at 90°C for 30 min to obtain a stable dispersion.
[0083] Step 3: Pour the dispersion obtained in step 2 into a mold and pre-freeze it in a refrigerator at a pre-freezing temperature of -10°C for 6 hours.
[0084] Step 4: Take out the sample from step 3 and place it in a freeze dryer for vacuum freeze drying to obtain an aerogel material. The vacuum degree of this process is 15 Pa, the vacuum freeze drying temperature is -55°C, and the time is 48 hours.
[0085] Step 5: Compound the sample in step 4 with the phase change material by vacuum impregnation. First, heat n-eicosane in a beaker at 70°C. After the n-eicosane is completely melted, place the prepared aerogel into the melted n-eicosane, and then place the beaker in a vacuum oven for insulation at 70°C for 4 hours. Under negative pressure, liquid n-eicosane fully penetrates into the pores of the aerogel. After filling the aerogel with n-eicosane, filter out the excess n-eicosane liquid on the surface in a ceramic funnel. Finally, a composite phase change material prepared by aerogel is obtained.
[0086] Test results: The mass ratio of the obtained composite phase change material aerogel is 3.5%, and the mass ratio of n-eicosane is 96.5%. It can be seen from the SEM image that the aerogel is well arranged, presents continuous wrinkles, has a bridge-like structure, forms a continuous and interconnected 3D network, and there is no obvious dividing line between the aerogel wrinkles after filling the phase change material, indicating that n-eicosane has been completely filled into the microporous structure. It can be seen from the XRD and FT-IR spectra that no new peaks appear except for the characteristic peaks of CNTs and PVA, indicating that PVA has no effect on the crystal structure of n-eicosane. It can be seen from the DSC graph that the melting phase change enthalpy and crystallization phase change enthalpy of the phase change aerogel material reach 195.2J / g and 192.0J / g respectively, the melting temperature and crystallization temperature are 37.0℃ and 31.4℃ respectively, and the corresponding encapsulation rate is 86.3%. The light-to-heat conversion efficiency of Example 5 is increased by 354.3% compared with that of the sample in Example 1, reaching 97.71%, which is the most efficient sample among all the embodiments.
[0087] Comparative Example 1 (adding only MXenes):
[0088] Step 1: Weigh 300 mg of boric acid and add it to 50 mL of deionized water, stir for 10 min to obtain a 6 mg / mL boric acid solution. Then add 4000 mg of PVA to 100 mL of deionized water, stir at 90 ° C for 30 min to obtain a 40 mg / mL PVA solution. Then add the boric acid solution to the 40 mg / mL PVA solution, stir at 90 ° C for 10 min to form a uniform PVA mixture.
[0089] Step 2: Take 15 mL of the PVA mixed solution obtained in step 1 into a beaker, add 7 mL of MXenes solution (the concentration of the MXenes solution is 5 mg / mL), and finally add 10 mL of deionized water, heat and stir at 90°C for 30 min to obtain a stable dispersion.
[0090] Step 3: Pour the dispersion obtained in step 2 into a mold and pre-freeze it in a refrigerator at a pre-freezing temperature of -10°C for 6 hours.
[0091] Step 4: Take out the sample from step 3 and place it in a freeze dryer for vacuum freeze drying to obtain an aerogel material. The vacuum degree of this process is 15 Pa, the vacuum freeze drying temperature is -55°C, and the time is 48 hours.
[0092] Step 5: Compound the sample in step 4 with the phase change material by vacuum impregnation. First, heat n-eicosane in a beaker at 70°C. After the n-eicosane is completely melted, place the prepared aerogel into the melted n-eicosane, and then place the beaker in a vacuum oven for insulation at 70°C for 4 hours. Under negative pressure, liquid n-eicosane fully penetrates into the pores of the aerogel. After filling the aerogel with n-eicosane, filter out the excess n-eicosane liquid on the surface in a ceramic funnel. Finally, a composite phase change material prepared by aerogel is obtained.
[0093] The melting phase change enthalpy and crystallization phase change enthalpy of the phase change aerogel material reach 184.1 J / g and 183.0 J / g respectively, and the melting temperature and crystallization temperature are 37.5°C and 31.1°C respectively.
[0094] From the above examples 1 to 5 and comparative example 1, it can be seen that:
[0095] (1) According to the MXenes / CNTs modified aerogel composite phase change material prepared in the above-mentioned Examples 2 to 5, based on 100% by mass, the mass percentage of MXenes / CNTs modified aerogel is 3.0-4.4%, the mass percentage of phase change material is 95.6-97.0%, and the photothermal conversion efficiency is increased from 21.51% in Example 1 (excluding MXenes and CNTs) to 89.13% to 97.71%, indicating that the addition of CNTs and MXene significantly improves the photothermal conversion efficiency of the phase change composite material.
[0096] (2) The phase change enthalpy of the aerogel phase change material of Example 1 (without MXenes and CNTs) is 209.1 J / g, and the phase change enthalpy of the phase change composite aerogel material obtained by adding only MXenes in Comparative Example 1 is 184.1 J / g, which is significantly decreased. The phase change enthalpy of the MXenes / CNTs modified aerogel composite phase change material prepared according to Examples 2 to 5 shows a gradient downward trend, which is 195.2 to 210.0 J / g, indicating that the addition of CNTs improves the defect of the modified aerogel composite phase change material obtained by adding only MXenes, which has a significant decrease in phase change enthalpy.
[0097] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A phase-change composite aerogel material for photothermal conversion and high-density heat storage, characterized in that: It is a phase change composite aerogel material with MXenes / CNTs modified aerogel as a three-dimensional porous continuous supporting skeleton and phase change material as a filling material; wherein, the mass percentage of the phase change composite aerogel material is 100%, the mass percentage of the MXenes / CNTs modified aerogel is 3.0-4.4%, and the mass percentage of the phase change material is 95.6-97.0%.
2. The phase-change composite aerogel material for photothermal conversion and high-density heat storage according to claim 1, characterized in that: The phase change enthalpy value of the phase change composite aerogel material is 195.2-210.0 J / g, and the encapsulation rate is greater than 85%.
3. The phase-change composite aerogel material for photothermal conversion and high-density heat storage according to claim 1, characterized in that: The phase change material is selected from one or more of monohydric alcohol phase change materials, straight-chain alkane phase change materials, and fatty acid phase change materials. The monohydric alcohol phase change material is selected from one or more of dodecanol, tridecanol, tetradecanol, pentadecanol, and hexadecanol. The straight-chain alkane phase change material is selected from one or more of paraffin, n-pentadecane, n-hexadecane, n-heptadecane, n-octadecane, n-nonadecane, and n-eicosane. The fatty acid phase change material is selected from one or more of palmitic acid, stearic acid, lauric acid, myristic acid, and palmitic acid. Preferably, the phase change material is n-eicosane.
4. The phase-change composite aerogel material for photothermal conversion and high-density heat storage according to claim 1, characterized in that: The MXenes are selected from Ti2C MXenes, Ti3C2 MXenes, Ti3CN MXenes, V2C MXenes, Nb2C MXenes, TiNbC MXenes, Nb4C3 MXenes, Ta4C3 MXenes, (Ti 0.5 Nb 0.5 )2C MXenes and (V 0.5 Cr 0.5 )One or more of 3C2MXenes; preferably, the MXenes are Ti3C2 MXenes.
5. The phase-change composite aerogel material for photothermal conversion and high-density heat storage according to claim 1, characterized in that: The CNTs are selected from one or more of multi-walled carbon nanotubes, single-walled carbon nanotubes, carboxylated carbon nanotubes and amino-treated carbon nanotubes.
6. A method for preparing a phase-change composite aerogel material for photothermal conversion and high-density heat storage as claimed in any one of claims 1 to 5, characterized in that: The steps include: Step (1), adding boric acid and polyvinyl alcohol (PVA) into deionized water, stirring and heating, to obtain a PVA mixed solution; Step (2), adding the PVA mixed solution, CNTs, and MXenes dispersion into deionized water in proportion, stirring and heating, to obtain a stable dispersion; Step (3), transferring the dispersion obtained in step (2) into a mold, first pre-freezing it, and then performing vacuum freeze drying to obtain an aerogel material; Step (4), impregnating the aerogel material obtained in step (3) into the phase change material in a molten state by vacuum impregnation to obtain a phase change composite aerogel material.
7. The preparation method according to claim 6, characterized in that: In step (1), the mass ratio of boric acid to polyvinyl alcohol (PVA) is (1-5): (10-30), and the concentration of the formed PVA mixed solution is 30-50 mg / mL; in step (2), the concentration of the MXenes dispersion is 3-7 mg / mL, the volume ratio of the PVA mixed solution, the MXenes dispersion and deionized water is 1: (0.01-0.47): (0.2-0.67), and the mass ratio of MXenes to CNTs is (1-7):
6.
8. The preparation method according to claim 6, characterized in that: In step (1), boric acid and polyvinyl alcohol (PVA) are first dissolved in deionized water respectively, and then the boric acid solution and the PVA solution are mixed, and stirred at 80-100° C. for 5-15 minutes to form a uniform PVA mixed solution; in step (2), the mixture is stirred at 80-100° C. for 30-40 minutes; in step (3), the pre-freezing treatment temperature is -20° C., the pre-freezing treatment time is 5-7 hours, the vacuum freeze drying temperature is -50° C. to -60° C., the vacuum freeze drying time is 45-55 hours, and the vacuum degree is not greater than 15 Pa; in step (4), the vacuum degree of vacuum impregnation is not greater than 20 Pa, the time is 3-5 hours, and the temperature is 60-80° C.
9. A phase change composite aerogel material prepared by the preparation method according to any one of claims 6 to 8.
10. Use of the phase change composite aerogel material according to claim 9 in solar thermal conversion and heat storage materials.
Citation Information
Patent Citations
Light-heat energy conversion and heat energy storage shape-stabilized phase-change compound material and production method thereof
CN109852349A
Method for preparing heat conduction material
CN110272611A
Heat conduction enhanced heat energy storage shape-stabilized phase-change composite material and preparation method thereof
CN110684510A
Light and heat storage type composite phase change material for energy storage and preparation method of light and heat storage type composite phase change material
CN113136172A
Wearable photo-thermal phase change energy storage composite film and preparation method thereof
CN116574298A
Cited By
Bentonite-regulated solar-driven light-heat-electricity conversion composite phase change material as well as preparation method and application of bentonite-regulated solar-driven light-heat-electricity conversion composite phase change material
CN121574710A
Bentonite-regulated solar-driven light-heat-electricity conversion composite phase change material, and preparation method and application thereof
CN121574710B